2023
DOI: 10.22441/indikator.v7i1.18396
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Overconfidence Bias and Representativeness Bias on Investment Decision With Risk Tolerance as Mediating Variable

Abstract: This research is intended to determine the effect of overconfidence bias and representative bias on investment decisions with risk tolerance as a mediating variable. The object of this research is investors who invest in the Indonesian Capital Market. The technique of collecting data is by using a questionnaire through online media and a literature study with the criteria of active investors with a sample of 200 investors. Data analysis in this study uses an alternative method of Structural Equation Modeling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 0 publications
0
2
0
7
Order By: Relevance
“…The positive thinking and confidence is also beneficial for the company in stock exchange because more and more investors that will put their capital in a certain company, hence it will open more opportunities to success. The understanding the Representativeness Bias positively impacts the investment decision is in accordance with the findings of the studies undertaken by [3], [10], [11], [21], [22] and [23] which showed that Representativeness Bias have positive impacts towards investment decision. Based on this findings, second hypothesis could be formulated as follows: H.2 : Representativeness Bias have positive impacts on investment decision.…”
Section: The Role Of Risk Tolerance In Mediating the Effect Of Overco...supporting
confidence: 89%
See 4 more Smart Citations
“…The positive thinking and confidence is also beneficial for the company in stock exchange because more and more investors that will put their capital in a certain company, hence it will open more opportunities to success. The understanding the Representativeness Bias positively impacts the investment decision is in accordance with the findings of the studies undertaken by [3], [10], [11], [21], [22] and [23] which showed that Representativeness Bias have positive impacts towards investment decision. Based on this findings, second hypothesis could be formulated as follows: H.2 : Representativeness Bias have positive impacts on investment decision.…”
Section: The Role Of Risk Tolerance In Mediating the Effect Of Overco...supporting
confidence: 89%
“…The result of this study strengthen previous studies that shows the positive influence of Overconfidence Bias towards investment decision, including those undertaken by [3], [4], [5], [6], [11], [18] and [24]. On the contrary, the finding of this study does not support the studies that found that Overconfidence Bias does not have any influence on investment decision, as those undertaken by [8], [9] and [20].…”
Section: The Role Of Risk Tolerance In Mediating the Effect Of Overco...contrasting
confidence: 70%
See 3 more Smart Citations